Toll-Like Receptors Recognize Intestinal Microbes in Liver Cirrhosis - Fan, Yujing; Li, Yunpeng; Chu, Yanjie; Liu, Jing; Cui, Lin; Zhang, Dekai (Frontiers in Immunology, 2021)
Liver cirrhosis is one major cause of mortality in the clinic, and treatment of this disease is an arduous task. The scenario will be even getting worse with increasing alcohol consumption and obesity in the current lifestyle. To date, we have no medicines to cure cirrhosis. Although many etiologies are associated with cirrhosis, abnormal intestinal microbe flora (termed dysbiosis) is a common feature in cirrhosis regardless of the causes. Toll-like receptors (TLRs), one evolutional conserved family of pattern recognition receptors in the innate immune systems, play a central role in maintaining the homeostasis of intestinal microbiota and inducing immune responses by recognizing both commensal and pathogenic microbes. Remarkably, recent studies found that correction of intestinal flora imbalance could change the progress of liver cirrhosis. Therefore, correction of intestinal dysbiosis and targeting TLRs can provide novel and promising strategies in the treatment of liver cirrhosis. Here we summarize the recent advances in the related topics. Investigating the relationship among innate immunity TLRs, intestinal flora disorders, and liver cirrhosis and exploring the underlying regulatory mechanisms will assuredly have a bright future for both basic and clinical research.